2009
DOI: 10.4103/0377-4929.54990
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of C4d immunostaining in the detection of the humoral component of renal allograft rejection and therapeutic implications

Abstract: C4d staining is a useful adjunct to routine histopathological methods in evaluating the humoral component of acute renal allograft dysfunction and helps in planning appropriate antirejection therapy with the goal of achieving long-term graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Out of these, 81% were of presumptive antibody mediated rejection P-AbAR/ AMR (6). Analysis of C4d immunostaining shows agreement quite well with various histopathological findings for AMR (11). Comparing renal transplant recipients with and without AMR, patients exhibiting subclinical AMR (C4d positivity and capillaritis/glomerulitis) in their first biopsy were found to be at an increased risk of more intense chronic lesions in their follow-up biopsies (17).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Out of these, 81% were of presumptive antibody mediated rejection P-AbAR/ AMR (6). Analysis of C4d immunostaining shows agreement quite well with various histopathological findings for AMR (11). Comparing renal transplant recipients with and without AMR, patients exhibiting subclinical AMR (C4d positivity and capillaritis/glomerulitis) in their first biopsy were found to be at an increased risk of more intense chronic lesions in their follow-up biopsies (17).…”
Section: Introductionsupporting
confidence: 54%
“…Histopathologic assessment of post-transplant renal biopsies was routinely performed in many centers. Detection of C4d in renal allograft biopsy by IF in combination with routine histopathological examination is now the gold standard for AMR (6,11,12). Banff group of nephrologists and transplant pathologists is leading body for updating classification of renal allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] In India, there are two published reports on C4d immunostaining. [45] The present study is our data of C4d immunostaining in non-protocol-indicated renal allograft biopsies. However, serological donor antibodies (DSA) were not available for any of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The role of C4d immunostaining in renal allograft biopsies has been published from India earlier. [45] In this study we analyzed the pattern of C4d staining in all renal allograft biopsies done for graft dysfunction.…”
Section: Introductionmentioning
confidence: 99%